KEBIJAKAN PENGEMBANGAN UNIT USAHA BADAN USAHA MILIK DESA (BUM Desa) SEROJA DESA MARSAWA KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2018-2020 - Gianda Pratama; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Seroja Village Owned Enterprise (BUM Desa) Development Policy has resulted in various problems within the Marsawa village environment. The policy of developing the BUM Desa Seroja business unit in the selection of business units is not appropriate. There is an overlap of the BUM Desa business with the village community. The existing business units in the BUM Desa Seroja have not had a major impact on improving the economy of the Marsawa Village community. Overlapping BUM Desa business units with the community have a negative impact on community businesses. The purpose of this study was to determine the impact of the policy on developing the Village Owned Enterprise (BUM Desa) Seroja Village Business Unit, Marsawa Village, Sentajo Raya District, Kuantan Singingi Regency in 2018-2020. This study uses Good Corporate Governance Theory (KNKG: 2006) Good Corporate Governance consists of 5 principles of Transparency, Accountability, Responsibility, Independence, Equality and Fairness. The research method used is qualitative research. This type of research is descriptive qualitative research. The research location is in Marsawa Village, Sentajo Raya District, Kuantan Singingi Regency. The results of the study prove that the development of the Village Owned Enterprise (BUM Desa) Seroja Desa Marsawa resulted in overlapping with the community business unit so that the impact on the community of business actors who were the same as the BUM Desa Seroja business unit felt disadvantaged and for the impact of BUM Desa on the level of The welfare of the community is still not good but the BUM Desa Seroja has been able to provide PADes and social assistance to the people of Marsawa Village every year, and open up job opportunities. Keywords: Policy, Development, Impact, BUM Desa.